Effects of hawthorn (Crataegus oxycantha) fruit extract on tibia bone properties in broiler chickens subjected to heat stress - Kaya, H; Karaalp, M (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to investigate the effects of different doses of hawthorn (Crataegus oxyacantha) fruit extract (HFE) supplementation to experimentally heat stressed broiler drinking water on tibia morphology, biomechanics and mineral levels. 300 one-day-old male broiler were randomly allocated to 6 experimental groups according to 2x3 factorial experimental design with two different ambient temperatures (24 and 35oC) and three different HFE additions (0, 0.2 and 0.4 mL/L). Each experimental group contained five replicates of 10 chicks each. Heat stress (HS) decreased tibia dry weight, length, wet weight, volume, seedor index, cortex thickness, shear force and shear stress and increased dry matter percentage (P<0.05). HS also caused a decrease in tibia Ca, Mg, Cu, Fe, Zn and K (P<0.05) levels. The addition of HFE to the water of broilers housed under HS didn’t affect the morphological and biomechanical properties of tibia. Ca level of tibia increased with 0.2 mL/L HFE addition and Mg and Zn levels increased with both 0.2 and 0.4 ml/L HFE additions compared to the control (P<0.05), while Fe and Mn levels of tibia decreased with 0.2 mL/L HFE addition and K level decreased with both levels of HFE addition compared to the control (P<0.05). On the other hand, tibia Cu level decreased with 0.2 mL/L HFE addition and increased with 0.4 mL/L HFE addition. It was concluded that the addition of 0.2 mL/L HFE to the water of broilers exposed to high ambient temperature would be sufficient and recommendable to improve bone quality characteristics.